THE USE OF TRANSLATION IN TEACHING LISTENING FOR THE ELEVENTH GRADE AT SMA NEGERI 2 KISARAN - Nana Yunita; Masitowarni Siregar; Siti Aisah Ginting (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
This study focused on the use of tanslation in teaching listening for the eleventh grade. The aim of this study was to describe the use of translation and analyze the reasons of using translation in teaching listening grade eleventh at SMA Negeri 2 Kisaran. This study was qualitatively conducted that taken from one english teacher of SMA Negeri 2 Kisaran. The data were collected by using recording, interviewing and observing the whole processes of teaching listening. The findings of this study showed that there were 34 times of using translation found during three processes that they were conveying and checking meaning of words or sentences, explaining grammar and classroom management. The reasons of using translation in teaching listening were facilitating communication, teacher- student relationship and the L2 learning. The findings of this study revealed that translation contributed to the study of foreign language teaching especially teaching listening.